2024
DOI: 10.1021/acsnano.3c11408
|View full text |Cite
|
Sign up to set email alerts
|

Joule-Heating-Driven Synthesis of a Honeycomb-Like Porous Carbon Nanofiber/High Entropy Alloy Composite as an Ultralightweight Electromagnetic Wave Absorber

Shipeng Wang,
Qiangchun Liu,
Shikuo Li
et al.

Abstract: High entropy alloys (HEA) have garnered significant attention in electromagnetic wave (EMW) absorption due to their efficient synergism among multiple components and tunable electronic structures. However, their high density and limited chemical stability hinder their progress as lightweight absorbers. Incorporating HEA with carbon offers a promising solution, but synthesizing stable HEA/carbon composite faces challenges due to the propensity for phase separation during conventional heat treatments. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 63 publications
0
0
0
Order By: Relevance
“…The entropy values for the prepared electrocatalyst have been supplemented in the revised manuscript. According to previous literature reports, the calculation of entropy can be achieved by where R is the molar gas constant and x represents the total mole constant of the elemental component.…”
Section: Methodsmentioning
confidence: 99%
“…The entropy values for the prepared electrocatalyst have been supplemented in the revised manuscript. According to previous literature reports, the calculation of entropy can be achieved by where R is the molar gas constant and x represents the total mole constant of the elemental component.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, research has indicated that Joule heating can be utilized in the synthesis of high-entropy alloys and carbon composites, resulting in materials that exhibit excellent electromagnetic wave absorption. 106 Consequently, in the field of EMI shielding and microwave absorption material preparation, CJH technology can enhance the conductivity of the material, optimise the structure of its carbon-based nano-part, endow the material with abundant defects and pore structures, and increase the specific surface area of the material, thus enhancing its ability to scatter or absorb electromagnetic waves.…”
Section: Cjh For the Preparation Of Carbon-based Nanomaterialsmentioning
confidence: 99%